Research anthology on mental health stigma, education, and treatment (Medical Information Science Reference, IGI Global, 2021)
"This book explores the latest research on the newest advancements in mental health, best practices and new research on treatment, and the need for education and awareness to mitigate the stigma that surrounds discussions on mental health by providing chapters that cover new technologies that are impacting delivery modes for treatment, the latest methods and models for treatment options, how education on mental health is being both delivered and developed, and how mental health is viewed and discussed when society is facing uncertainty and crisis"--